HepG2 Cell Resistance against Camptothecin from a Lysosomal Drug Delivery. Issue 12 (1st October 2015) - Lee, Hoyeon; Uhm, Soojin; Shin, Jung‐Won; Jeon, Hyun Mi; Dongbang, Sun; Jung, Hyo Sung; Na, Yun‐Cheol; Kang, Chulhun; Kim, Jong Seung
Abstract: A galactose‐appended drug delivery system released camptothecin (CPT) to lysosomes of HepG2 hepatoma cells, resulting in the cell resistance to the anticancer drug. We found that the resistance to CPT is caused by alteration of the drug release from the prodrug in lysosomes, emphasizing that the final delivery locations may critically influence drug efficacy. Abstract : Try to resist : The study of HepG2 cell resistance against camptothecin (CPT) using a galactose‐appended drug delivery system was successfully performed. The system released CPT to lysosomes of HepG2 hepatoma cells so that the lysosomal release of CPT led to the cell resistance to the anticancer drug.